0735 Which Self-Reported Sleep Health Characteristics Predict Mortality in Older Adults?. (27th April 2018) - Wallace, M; Stone, K; Redline, S; Hall, M; Buysse, D
Abstract: Introduction: Studies have shown that self-reported sleep characteristics predict mortality. However, studies commonly consider each sleep characteristic separately, even though the clinical reality is that sleep is multidimensional. We used a multidimensional sleep health framework to examine which self-reported sleep characteristics predict mortality in older adults. Methods: The sample included 4, 221 females and 3, 867 males ages 65–96 from the Study of Osteoporotic Fractures in Women, Osteoporotic Fractures in Men Sleep Study, and the Sleep Heart Health Study. Self-report questionnaires captured sleep midpoint, total sleep time (TST), sleep efficiency (SE), sleep latency, and sleepiness. We fit multivariable Cox models to examine associations between sleep characteristics and time to all-cause mortality. Men and women were considered separately to reduce confounding. Models were adjusted for 23 covariates including demographics, alcohol use, smoking, medical history, medications, and cohort. Results: Among women, longer TST and TST-squared were associated with mortality [Hazard Ratio, HR = 1.06 (1.01, 1.12) and 1.05 (1.03, 1.08)]. Women with ≥9 (versus 7) hours TST had 1.36 fewer years to 50% mortality. Among men, longer TST and lower SE increased mortality risk [HR =1.11 (1.05, 1.18) and 0.88 (0.82, 0.94)]. Men with ≥9 (versus 7) hours TST had 0.94 fewer years to 50% mortality. Men with the lowest SE (≤64% versus an average 88%) had 0.84 fewer years to 50% mortality. Conclusion: Long self-reported TST is associated with increased mortality risk in older adults. Low SE is associated with increased mortality risk in older males. Next steps are to compare the predictive power of multivariable versus univariable sleep health and consider objective sleep measures and other outcomes. Support (If Any): MrOS is supported by grants R01 HL071194, R01 HL070848, R01 HL070847, R01 HL070842, R01 HL070841, R01 HL070837, R01 HL070838, and R01 HL070839. SOF is supported by grants AG05407, AR35582, AG05394, AR35584, and AR35583. SHHS is supported by grants (U01HL53916, U01HL53931, U01HL53934, U01HL53937, U01HL53938, U01HL53940, U01HL53941, U01HL64360). Dr. Wallace is supported by NIA grant R01 AG056331. This work was also supported by the National Sleep Research Resource (NSRR) funded by NHLBI grant HL114473.